Where the jobs are. - Kariya, S.
The economic doldrums that officially began in 2001 may well linger into 2003. Although the jobless rate for US electrical and electronics engineers is down from an all time peak of 4.8%, it's still far from the mere 1.3% it was two years ago. The telecom and computer industries-home to many electrical engineers-were first and second respectively, in job cuts in 2002. Still, there are bright spots. The defense sector continues to fire on many cylinders, and that translates into hiring in areas such as intelligence technologies, defenses against chemical, biological, and nuclear weapons; and new battlefield systems such as smart bombs, unmanned air vehicles, and communications links. The US government showered the Defense Department with more than US
Keywords: Analog circuit design; Automated design tools; Automotive sales; Defense sector; Electrical engineers; Electronics engineers; Jobs; Mixed-signal circuit design; Power management; Semiconductor industry; Wireless sales